Analysis of multiple new-particle growth pathways observed at the US DOE Southern Great Plains Field Site - Hodshire, Anna, author; Pierce, Jeff, advisor; Barsanti, Kelley, committee member; Farmer, Delphine, committee member; Kreidenweis, Sonia, committee member (Colorado State University. Libraries, 2016)
New-particle formation (NPF) is a significant source of aerosol particles to the atmosphere. However, these particles are initially too small to have climatic importance and must grow, primarily through net uptake of low-volatility species, from diameters 1 nm to 30-100 nm in order to potentially impact climate. There are currently uncertainties in the physical and chemical processes associated with the growth of these freshly formed particles that lead to uncertainties in aerosol-climate modeling. Four main pathways for new-particle growth have been identified: condensation of sulfuric acid vapor (and associated bases when available), condensation of organic vapors, uptake of organic acids through acid-base chemistry in the particle phase, and accretion of organic molecules in the particle phase to create a lower-volatility compound that then contributes to the aerosol mass. The relative importance of each pathway is uncertain and may vary by geographic location and atmospheric conditions. Assessing the relative importance is the focus of this work. The 2013 New Particle Formation Study (NPFS) measurement campaign took place at the DOE Southern Great Plains (SGP) facility in Lamont, Oklahoma, during spring 2013. Measured gas-and particle-phase compositions during these new-particle growth events suggest three distinct growth pathways: (1) growth by primarily organics; (2) growth by primarily sulfuric-acid/ammonia; and (3) growth by primarily sulfuric-acid/bases/organics. To supplement the measurements, we used the particle-growth model MABNAG (Model for Acid-Base chemistry in NAnoparticle Growth) to gain further insight into the growth processes on these three days at SGP. MABNAG simulates growth from (1) sulfuric-acid condensation (and subsequent salt formation with ammonia or amines); (2) near-irreversible condensation from non-reactive extremely-low-volatility organic compounds (ELVOCs); and (3) organic-acid condensation and subsequent salt formation with ammonia or amines. MABNAG is able to corroborate the observed differing growth pathways, while also predicting that ELVOCs contribute more to growth than organic salt formation. However, most MABNAG model simulations tend to underpredict the observed growth rates between 10-20 nm in diameter; this underprediction may come from neglecting the contributions to growth from semi-to-low-volatility species or accretion reactions. Our results suggest that in addition to sulfuric acid, ELVOCs are also very important for growth in this rural setting. We discuss the limitations of our study that arise from not accounting for semi- and low-volatility organics, as well as nitrogen-containing species beyond ammonia and amines in the model. Quantitatively understanding the overall budget, evolution, and thermodynamic properties of lower-volatility organics in the atmosphere will be essential for improving global aerosol models.
Keywords: aerosol measurements; aerosols; aerosol chemistry; growth pathways; aerosol modelling